Improved flexible ZnO/CsPbBr3/Graphene UV photodetectors with interface optimization by solution process. (October 2020) - Liu, Shuting; Liu, Xuhai; Zhu, Zhengfeng; Wang, Shalong; Gu, Yu; Shan, Fukai; Zou, Yousheng
Graphical abstract: We use a simple solution strategy of constructing flexible thin film PDs based on PVDF substrate with the structure of ZnO NWs/CsPbBr3 NSs/graphene. The built-in electric field due to PN junction of ZnO and CsPbBr3 can facilitate the separation and transport of the photo-generated carriers. Moreover, the ZnO networks filled with the CsPbBr3 NSs in the surface result in a smooth interface, which further promotes the charge carrier transport and leads to excellent device performance. The PDs with remarkable flexibility can be easily attached to the human bodies for the wearable application. Highlights: The flexible and wearable ZnO/CsPbBr3 PN junction PD is fabricated via a solution method. CsPbBr3 NSs result in a smooth interface and close contacts between ZnO and graphene and enhance the carriers transport. The Ilight /Idark ratio can reach as high as ∼10 3 by optimization of the ZnO/CsPbBr3 interface. The PDs have excellent flexibility and stability under serious bending conditions. Abstract: Flexible and wearable photodetectors (PDs) that can be directly equipped on human bodies have attracted extensive attention due to their great potential in communication, health and safety applications. However, low flexibility and complicated fabrication process hinder the development of fiber- and textile-PDs for practical applications. Here, we use an efficient solution strategy to integrate CsPbBr3 nanosheets (NSs) into conventional ZnO nanowires (NWs)/graphene flexible thin film PDs based on PVDF substrate. Compared with the simpler ZnO NWs/graphene structure, the built-in electric field of ZnO/CsPbBr3 PN junction can facilitate the separation and transport of the photo-generated carriers. Moreover, the ZnO networks filled with CsPbBr3 NSs result in a smooth interface and close contacts with graphene. With the interface optimization, the enhanced transport efficiency of the carriers further leads to a high Ilight /Idark ratio of ∼10 3 . In addition, such PVDF based PDs exhibit excellent flexibility, demonstrating great potential for practical flexible optoelectronics.